Producing the Product: A Case Study of Law and Its Absence. (3rd November 2017) - Carr, Helen; Cowan, Dave; Wallace, Alison
Abstract : In this article, we seek to develop socio‐legal studies through a rupturing of the ideas behind the social and the legal, ideas that are most often presumed to exist and are used to explain that which is already there. The ubiquity of law and the omniscience of society have become givens. We use a product called shared ownership as a case study, arguing that the product was given life by a legal document (the lease) which itself represented the translation of a range of different perspectives and audiences (albeit not the consumer), and which, itself, has been translated, most notably in a 2008 High Court decision. That decision counterintuitively found that the lease had created an assured shorthold tenancy (albeit a long one) but, despite its threat to the product, has been largely ignored. We discuss the processes of, and reasons for, the translation through which that ignorance has been induced.